Synthesis and Characterisation of Thin Films of Bismuth Triiodide for Semiconductor Radiation Detectors. (2nd April 2014) - Garg, Alka; Tomar, Monika; Gupta, Vinay
Abstract : Bismuth iodide is a potentially active material for room temperature radiation detector, as it is well reported in the literature that it has both wide energy band gap and high atomic absorption coefficient. Crystalline films of high atomic number and high radiation absorption coefficient can absorb the X-rays and convert them directly into electrical charges which can be read by imaging devices. Therefore, it was proposed to grow thin films of Bismuth iodide on glass substrate using thermal evaporation technique in vacuum to avoid the inclusion of impurities in the films. The structural studies of the films were carried out using XRD and optical absorption measurement was carried out in the UV/VIS region using spectrophotometer. All Bismuth iodide films grown at room temperature are polycrystalline and show X-ray diffraction peaks at angles reported in research papers. The optical transmission spectra of BiI3 films show a high transmission of about 80% in visible region with a sharp fall near the fundamental absorption at 650 nm. Resistivity of the as-grown film was found to be around 10 12  ohm-cm suitable value for X-ray detection application. Films were subjected to scanning electron microscopy to study the growth features of both as-grown and annealed films.